The Effect of Autumnal Moth Induced Volatile Organic Compound Emissions to Aerosol Load in Subarctic Region - Ylivinkka, Ilona (Helsingin yliopisto, 2019)
Volatile organic compounds (VOCs) are hydrocarbons that are emitted to the atmosphere from biogenic or anthropogenic sources. Plants emit VOCs as a part of normal metabolism, but the emissions are significantly increased under stressed conditions. For example heat wave, drought and herbivory cause stress for the plants. Laboratory studies have shown that VOCs emitted by herbivory infested boreal forest trees have enhanced secondary organic aerosol (SOA) production. In this study, 25 years (1992–2016) of atmospheric data from measurement site in eastern Finnish Lapland was analyzed to understand wheter the enhancement is atmospherically relevant. The knowledge is important, as aerosol particles cause changes in radiative forcing, and thus contribute to the climate change. At the study site autumnal moth (Epirrita autumnata) larvae are prominent defoliator of mountain birches (Betula pubescens spp. czerepanovii). Autumnal moths have cyclic population dynamics, and during the severe population outbreaks, they can consume all the leaves of mountain birches in vast regions. Despite the severity of the herbivory to the local ecosystem, the analysis did not show connection between the number of autumnal moths and aerosol processes. Also, no clear correlation between the total number concentration and temperature, and hence the basal VOC emissions from biogenic sources, was observed. Nor did sulfur dioxide or sulfuric acid concentration have strong correlation with total particle concentration which would have been expected. The results indicate that probably the total biomass of mountain birches is too small to cause detectable changes in atmospheric variables. Additionally, the study period had only one severe population outbreak during which the data availability of atmospheric variables was limited. However, climate change proceeds fast in the Arctic region. Hence, the basal VOC emissions from vegetation will increase. Also, both the mountain birches and new moth species will expand to the areas where they did not ...